Does Shareholder Composition Matter? Evidence from the Market Reaction to Corporate Earnings Announcements - Hotchkiss, Edith S.; Strickland, Deon (Journal of Finance, 2003)
ABSTRACT We examine whether institutional ownership composition is related to parameters of the market reaction to negative earnings announcements. When firms report earnings below analysts' expectations, the stock price response is more negative for firms with higher levels of ownership by momentum or aggressive growth investors. There is no evidence, however, that these institutions cause an “overreaction” to earnings news. Ownership structure is also related to trading volume and to stock price volatility on days around earnings announcements. Our findings are consistent with the idea that the composition of institutional shareholders effects stock price behavior around the release of corporate information.